Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1523/jneurosci.22-22-09785.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Synaptically Released β-Amyloid Accumulates as Extracellular Deposits in the Hippocampus of Transgenic Mice

Abstract: A neuropathological hallmark of Alzheimer's disease is the deposition of amyloid-beta (Abeta) peptides in senile plaques in the hippocampus and cerebral cortex. Abeta is derived from larger integral membrane proteins termed amyloid precursor proteins (APP). We demonstrated previously that APP, synthesized by neurons in the entorhinal cortex, is transported via the perforant pathway to presynaptic terminals in the dentate gyrus. We reported that, although full-length APP and membrane-tethered, C-terminal APP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
215
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(245 citation statements)
references
References 52 publications
26
215
2
2
Order By: Relevance
“…APP is transported along axons to presynaptic terminals where it accumulates at relatively high levels which can result in Aβ deposition at synpases 72 . One possible function of full-length APP is as a cell surface receptor that transduces signals within the cell in response to an extracellular ligand 73 .…”
Section: Boxmentioning
confidence: 99%
“…APP is transported along axons to presynaptic terminals where it accumulates at relatively high levels which can result in Aβ deposition at synpases 72 . One possible function of full-length APP is as a cell surface receptor that transduces signals within the cell in response to an extracellular ligand 73 .…”
Section: Boxmentioning
confidence: 99%
“…7B). A major secretion site of Ab seems to be distal axons/synapses (Lazarov et al 2002;Sheng et al 2002), but recently it was reported that Ab can be secreted from axons and dendrites and can elicit local effects on neighboring neurons ( Fig. 7C; Wei et al 2010).…”
Section: Subcellular Sites Of G-secretase-mediated App Processingmentioning
confidence: 99%
“…Parallel studies in animal models and cell culture have linked APP transport, neuronal activity, and Ab metabolism. APP is axonally transported from the entorhinal cortex to the hippocampal formation via the perforant pathway (Buxbaum et al 1998a), and lesions of this pathway in transgenic mice overexpressing FAD-linked mutant APP and PS1 transgenes results in substantially less Ab deposition within the hippocampus (Lazarov et al 2002). Early studies showed that electrical depolarization increases the release of soluble APP-a in rat hippocampal brain slices (Nitsch et al 1993), and it appears that these effects are mediated by activation of muscarinic M1 acetylcholine receptors which leads to parallel decreases in Ab levels (Beach et al 2001;Hock et al 2003).…”
Section: Activity-dependent App Processingmentioning
confidence: 99%
“…Because CBF neurons are also an early target for NFT formation (77,78), a double-label PHFtau and choline acetyltransferase immunocytochemistry paradigm combined with single-cell mRNA analysis is a future direction that may help elucidate early alterations in these selectively vulnerable populations within the basal forebrain. Finally, the presence of extracellular SPs in the terminal fields of cholinergic innervation within the neocortex and hippocampus of AD brain suggests that alterations in the metabolism and transport of APP in CBF neurons may play a role in plaque formation (79,80), as evidenced by axotomy paradigms in mouse models of amyloid deposition where reduction of amyloid accumulation is observed on the side ipsilateral to the lesion (81)(82)(83).…”
Section: Single-cell Analysis In Ad: Choliner-gic Basal Forebrain (Cbmentioning
confidence: 99%